(untitled) (Journal of the College of Basic Education, 2023)
The dispersions of the refractive indices of (PMMA doped red methyl) films Irradiated by Gamma Rays have been determined using the Wemple-DiDomenico model . The oscillator energy E0 , dispersion energy Ed , absorption coefficient and skin depth are calculated before and after irradiated . Drude’s theory of dielectrics used to calculate carrier concentration Nopt . It’s found that Nopt increases after irradiation .